Studying Master’s or PhD on fully funded scholarship in East Asia – A great opportunity for Pakistani doctors - Shamim, Hafsa; Rehman, Iqra; Rehan, Sameen (Journal of the Pakistan Medical Association, 2025)
Dear Madam, We are writing this letter to inform doctors and medical students about fully-funded scholarship opportunities in East Asia, offering a pathway to non-clinical career options in high-quality academic institutions. In Pakistan, medical graduates increasingly face challenges in securing employment. The clinical career route is demanding, with specialization requiring at least four years of training after house job. Taking a foreign licensing exam (e.g., PLAB, USMLE) is also challenging due to additional financial constraints. Given these obstacles, the clinical career path can be difficult. Although only 7.9% (1) of final-year medical students and house officers in a Pakistani study indicated a preference for non-clinical specializations, we wish to present an alternative career pathway that can leverage doctors’ knowledge and skills beyond traditional clinical roles. Shifting to a non-clinical career path could help alleviate high unemployment rates among Pakistani doctors. Doctors can pursue a Master’s or PhD program in a basic science subject or degrees in non-clinical fields (e.g. MBA/Master in Clinical Research/Master of Public Health) abroad. Countries such as Japan, China and Korea grant prestigious fully funded government scholarships – MEXT Scholarship, CSC Scholarship and GKS Scholarship respectively - to international students. (2)(3)(4) These scholarships cover tuition fee, roundtrip airfare ticket, and a monthly allowance to cover living expenses. Depending on the program requirement, doctors may enrol directly in a PhD program depending on their career goals. While universities in the West offer fully funded scholarships, competition is often intense. East Asia, however, remains an untapped destination for Pakistani doctors. Around 95% of junior doctors prefer to move to Western countries like the USA, UK, Australia, and Canada. (5) This also means that East Asia is a land of opportunity. East Asian countries have a high standard of living and universities rank among the Top 100 QS World University Rankings. These countries offer a vibrant cultural experience. Furthermore, many Master’s and PhD programmes are taught in English. Upon completion of the degree, doctors can work in research, program management, healthcare administration, medical education, medical writing, health tech, entrepreneurship, etc. The authors have successful examples of doctors who took these opportunities and are now working as Assistant Professor, researchers and epidemiologist abroad, to name a few. —Continue